Peculiarities of Territorial Land Tenure in Conditions of Community Enlargement - Tovmasyan, L. G. (ՀԱԱՀ հիմնադրամ)
The article considers the peculiarities of territorial land tenure organization based on the example of enlarged communities in Lori marz. Upon the results of the surveys the issues of quantitative changes in the boundaries of the administrative territorial units and their impact on the efficiency increase of land tenure have been assessed. The changes in consolidation coefficient of the community plots and their impact on the economic indices of land utilization have been studied. To improve the land tenure efficiency it is recommended to amend the RA SCREC decision No. 186-N 2010, which will promote the elimination of various planning and cartographic errors in the cadastral maps and plans.
Keywords: Agricultural Engineering